HUBUNGAN ANTARA KARAKTERISTIK, NILAI, DAN KEPUASAN NASABAH (Studi di PT Panin Bank Cabang Pembantu Boyolali) - Sutarno - - (Universitas Slamet Riyadi, 2013)
ABSTRACT This study aims to examine the relationship between (1) characteristics of the customer and the customer value, (2) characteristics of the customer and the customer satisfaction, and (3) customer value and the customer satisfaction in PT Panin Bank Branch Boyolali. Population PT Panin Bank Branch customers maid Boyolali Year 2012 some 658 people. Samples were taken in a proportional sampling as many as 60 people. The data collection technique using a questionnaire with validity and reliability. Data analysis techniques using Chi-Square test. The analysis showed: (1) relationship between the characteristics of customers and customer value is not significant (2) relationship between the characteristics of customers and customer satisfaction is not significant (3) relationship between the customer value and customer satisfaction significantly. Conclusion of the study (1) The first hypothesis that there is a relationship between the characteristics of customers and customer value PT Panin Bank Branch Boyolali, not truth, (2) The second hypothesis is that there is a relationship between the characteristics of the customer and customer satisfaction PT Panin Bank Branch Boyolali, not truth. (3) The third hypothesis is that there is a relationship between the customer value and customer satisfaction PT Panin Bank Branch Boyolali unsubstantiated. Keywords: Characteristics of the customer, Customer Value, Customer Satisfaction.